ChemInform Abstract: Phosphorus as a Carbon Copy and as a Photocopy: New Conjugated Materials Featuring Multiply Bonded Phosphorus. Issue 34 (1st August 2013) - Simpson, M. Cather; Protasiewicz, John D.
Abstract Review: 41 refs.